The French policy of immigrant integration: Return to laïcité - Xuedan Yao (CES Working Papers, 2022)
After the 2015 European refugee crisis, immigrant integration has reemerged as a pressing issue endangering France's social and political stability. France is one of the main asylum host countries in Europe. In the past few years, terrorist attacks have become more frequent in France, and the spread of xenophobia has led to a social crisis that threatens the country's national security. It has prompted France to consider returning to Laïcité in response to this situation. So the purpose of this paper is to analyze France's immigrant integration policy in 2020 and reveal the discourse of Laïcité and republican values in France.
Keywords: 330; Secularism; French Muslims; Immigrant integration